2023
DOI: 10.1111/liv.15527
|View full text |Cite
|
Sign up to set email alerts
|

Liver phenotypes in PCOS: Analysis of exogenous and inherited risk factors for liver injury in two European cohorts

Abstract: Background & Aims: Fatty liver disease (FLD) is common in women with polycystic ovary syndrome (PCOS). Here, we use non-invasive tests to quantify liver injury in women with PCOS and analyse whether FLD-associated genetic variants contribute to liver phenotypes in PCOS.Methods: Prospectively, we recruited women with PCOS and controls at two university centres in Germany and Poland. Alcohol abuse was regarded as an exclusion criterion. Genotyping of variants associated with FLD was performed using TaqMan How to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 38 publications
(86 reference statements)
3
14
0
Order By: Relevance
“…Of note, the language model did not have access to the original database and was not exposed to the raw data. Our primary goal was to generate a dataset comprising N = 500 fabricated patient records, which included genotyping results of MTARC1 rs2642438 variant, liver function tests (i.e., alanine aminotransferase, (ALT) and aspartate aminotransferase (AST)), sex hormone binding globulin (SHBG) and hepatic steatosis index (HSI) as previously reported in our study in PCOS patients 6 . ADA received instructions (i.e., a desired number of cases, genotype frequency and minor allele frequency (MAF)) to fabricate data that would reproduce the statistically significant results as specified in our previous research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the language model did not have access to the original database and was not exposed to the raw data. Our primary goal was to generate a dataset comprising N = 500 fabricated patient records, which included genotyping results of MTARC1 rs2642438 variant, liver function tests (i.e., alanine aminotransferase, (ALT) and aspartate aminotransferase (AST)), sex hormone binding globulin (SHBG) and hepatic steatosis index (HSI) as previously reported in our study in PCOS patients 6 . ADA received instructions (i.e., a desired number of cases, genotype frequency and minor allele frequency (MAF)) to fabricate data that would reproduce the statistically significant results as specified in our previous research.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we uncover another potential risk associated with the creation of a fake replication cohort intended to authenticate our previous research findings from the manuscript we previously published in Liver International. 6 …”
Section: Introductionmentioning
confidence: 99%
“…17 However, the role of HSD17B13 protein in human liver disease and the molecular mechanisms behind the protective impact of the HSD17B13 rs72613567 genetic variant on the risk of liver disease are still poorly understood. 18 The results by Smyk et al 14 together with the putative biological role of HSD17B13 prompted us to examine the impact of the HSD17B13 rs72613567 variant on circulating SHBG, total and estimated free testosterone levels 19 in more than 300,000 European participants from the UK Biobank population-based cohort stratified by sex (Table 1). As expected, in both sexes, the minor TA allele was associated with lower ALT levels.…”
Section: Fatty Liver Disease Genetic Risk Variants and Interference O...mentioning
confidence: 99%
“…13 In this issue of Liver International, Smyk and colleagues went further and investigated the impact of common genetic variants predisposing to or protecting against NAFLD on liver phenotypes in two independent European cohorts of adult women with PCOS (German cohort, n = 42; Polish cohort, n = 143). 14 They found that in the German cohort characterized by older age and more severe liver damage, carriers of the patatin-like phospholipase domaincontaining 3 (PNPLA3) p.I148M variant, the main genetic risk variant for NAFLD, had higher liver stiffness.…”
Section: Fatty Liver Disease Genetic Risk Variants and Interference O...mentioning
confidence: 99%
See 1 more Smart Citation